Visualizing Organophosphate Precipitation at the Calcite-Water Interface by in Situ Atomic-Force Microscopy - Wang, L.; Qin, L.; Putnis, C.; Ruiz-Agudo, E.; King, H.; Putnis, Andrew (2016)
Esters of phosphoric acid constitute a large fraction of the total organic phosphorus (OP) in the soil environment and, thus, play an important role in the global phosphorus cycle. These esters, such as glucose-6-phosphate (G6P), exhibit unusual reactivity toward various mineral particles in soils, especially those containing calcite. Many important processes of OP transformation, including adsorption, hydrolysis, and precipitation, occur primarily at mineral–fluid interfaces, which ultimately governs the fate of organophosphates in the environment. However, little is known about the kinetics of specific mineral-surface-induced adsorption and precipitation of organophosphates. Here, by using in situ atomic-force microscopy (AFM) to visualize the dissolution of calcite (1014) faces, we show that the presence of G6P results in morphology changes of etch pits from the typical rhombohedral to a fan-shaped form. This can be explained by a site-selective mechanism of G6P–calcite surface interactions that stabilize the energetically unfavorable (0001) or (0112) faces through step-specific adsorption of G6P. Continuous dissolution at calcite (1014)–water interfaces caused a boundary layer at the calcite–water interface to become supersaturated with respect to a G6P–Ca phase that then drives the nucleation and growth of a G6P–Ca precipitate. Furthermore, after the introduction of the enzyme alkaline phosphatase (AP), the precipitates were observed to contain a mixture of components associated with G6P–Ca, amorphous calcium phosphate (ACP)–hydroxyapatite (HAP) and dicalcium phosphate dihydrate (DCPD). These direct dynamic observations of the transformation of adsorption- and complexation-surface precipitation and enzyme-mediated pathways may improve the mechanistic understanding of the mineral-interface-induced organophosphate sequestration in the soil environment.